Comportamiento organizacional y su influencia en el desempeño laboral en las secretarias del Cuerpo de Bomberos de Vinces - Bustamante Luna, Leydi Tayli (2022)
The present case study were made out in the Vinces Fire Department specifically in the secretary area, which has as its primary objective to analyze the aspects that imply poor job performance where it mainly involves the business management carried out by the secretary of said institution, so that the results obtained through the techniques applied in this interview serve as a focus for the solutions that will favor the aforementioned problem, and in such a way that the reader of this work acquires more knowledge about the negative things that affect impulse a labor incompetence and also in positive aspects that contribute to the success of the organization. Regarding the problem, a public company was chosen as a research technique by which aspects were identified that influence the idea that an individual can have a very high job performance, but it is not lucrative because factors such as the work environment and the level of attitude of a secretary intervene when implementing activities efficiently.